Preface for the Special Issue of International Conference on Electronics, Control, Optimization and Computer Science ICECOCS’20 - Salma Azzouzi; Saoussen Cheikhrouhou; Abdessalam Ait Madi; Mohammed Talibi Alaoui (Statistics, Optimization & Information Computing, 2022)
The main contributions of [Stat. Optim. Inf. Comput. Vol. 10, No. 1 (2022)], consisting of nineteen papers selected and revised from the international conference ICECOCS’2020, are highlighted.